Transactions of the American Philosophical Society. (Philadelphia American Philosophical Society.)
"Held at Philadelphia for promoting useful knowledge."
Each volume bears also a distinctive title.
Imprint varies.
Kislak Collection: New ser., v. 55, pt. 6 (1965).
Issues published <1995-> lack new series designation.
Issued irregularly in parts.
Also issued online.
Keywords: Electronic journals